Preliminary study on the optimization of recombinant human transferrin expression in insect cells baculovirus system - M. Ongkudon, Clarence; Abdul-Rahman, Badarulhisam; Abdul-Aziz, Azila (2004)
Insect cells Baculovirus system is a promising artificial system for producing many biopharmaceuticals products. In this study, the expression profiles of recombinant human transferrin (rhTf), a model protein expressed in Sf9 insect cells monolayer and baculovirus culture were investigated. Time course expression profile of rhTf at various multiplicity of infection (MOI), seeding density (SD), time of infection (TOI), and harvest time (HT) were conducted as well as growth control (GC) for non infected Sf9 cells. Growth kinetics of non infected and infected Sf9 cells were also performed to monitor the progress of infection. SDS-PAGE, Western Blot, and ELISA analyses were utilized in this study to confirm the progress of the rhTf production. The data shows that maximum production of rhTf was between 24 to 72 hours post infection, at the seeding density of 1.6 x 106 viable cells/ml, infection at day 2 post culture, and MOI of 5. The maximum rhTf yield was 11.2 ïg/ml. The results suggested that rhTf yield could be increased further provided that the nutrient and cells density are not limiting.